A Rare Benign Multilobulated Floor of Mouth Lesion (London Journal of Medical and Health Research, 2025)
Rhabdomyomas are a rare and benign, slow growing tumour of the skeletal muscles. They are even further classified into cardiac and extracardiac types according to their location. Extracardiac rhabdomyomas can be further divided based on cellular differentiation, such as; fetal, genital, and adult subtype [1] . Adult Type Rhabdomyomas shown to have clinical predominance towards adult males and more commonly reported in the head and neck region as compared to other parts of the body. This type of benign tumour also has a high recurrence rate. In this case review we discuss a rare case of floor of mouth rhabdomyoma.